2023
DOI: 10.1155/2023/6859054
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Cervical Cancer, Risk Perception, and Practice of Pap Smear Test among Young Adult Women of Dhulikhel Municipality, Nepal

Ishwori Byanju Shrestha,
Sandesh Bhusal,
Manish Rajbanshi
et al.

Abstract: Background. Despite being one of the most preventable forms of cancer, cervical cancer remains an important public health problem, especially in developing countries. However, there is limited evidence regarding awareness and practice of screening for cervical cancer among women in resource-poor settings like Nepal. This study is aimed at assessing the awareness of cervical cancer, risk perception, and practice of Pap smear tests among adult women of Dhulikhel municipality of Kavreplanchowk district in Nepal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Awareness levels tend to be higher in more developed countries and regions with robust healthcare systems having access to greater information and better health services. The findings from a study conducted in Nepal demonstrated that around 54.3% women have heard about cervical cancer [ 35 ], while in Nigeria, Uganda, and India, several other studies reveal that the percentage of women who possess knowledge about cervical cancer ranged from 65% to 99% [ 36 38 ]. The relatively low awareness of breast cancer among women identified in our study underscores the urgent need for targeted awareness promotion, particularly among vulnerable and at-risk populations.…”
Section: Discussionmentioning
confidence: 99%
“…Awareness levels tend to be higher in more developed countries and regions with robust healthcare systems having access to greater information and better health services. The findings from a study conducted in Nepal demonstrated that around 54.3% women have heard about cervical cancer [ 35 ], while in Nigeria, Uganda, and India, several other studies reveal that the percentage of women who possess knowledge about cervical cancer ranged from 65% to 99% [ 36 38 ]. The relatively low awareness of breast cancer among women identified in our study underscores the urgent need for targeted awareness promotion, particularly among vulnerable and at-risk populations.…”
Section: Discussionmentioning
confidence: 99%